WIPO's Contribution to the Establishment of International Rules for the Protection of Intellectual Property Rights - Benhalima, Leila (Journal of Legal Studies and Researches, 2021)
The World Intellectual Property Organization (WIPO) operates within the United Nations specialized agency system as a forum for Member States to establish and coordinate rules and practices that protect intellectual property rights, It also provides information on intellectual property and means of awareness to all groups of people, with a view to ensuring that its benefits are recognized, well understood and accessible to all.